Design and Construction of an IoT-Based Automatic Chicken Coop Door Systemwith Scheduled Time Control and Remote Control - Parhanudin Parhan; Ahmad Fatoni Dwi Putra; Nuraqilla Waidha Bintang Grendis (LPPM Universitas Qamarul Huda Badaruddin, 2026)
This article discusses the design and development of an Internet of Things (IoT)-based automatic system with scheduled time controland remote access control. The Internet of Things (IoT) is a system consisting of hardware, software, and internet technology designed to facilitate human interaction and enable devices with IP addresses to utilize internet networks as a communication medium. IoT can be used to monitor various physical parameters, such as temperature, humidity, pressure, and motion, depending on the application requirements. Designing systems using IoT-based technology can simplify daily human activities, as demonstrated in this study, which applies IoT methods to design an automatic chicken coop door with scheduled time control and remote access capabilities.The proposed method successfully produced an automatic chicken coop door design that operates effectively using IoT technology. All major components, including the ESP8266 microcontroller, RTC module, servo motor, I2C LCD, breadboard, and the Blynk application, were successfully interconnected and operated in an integrated manner according to their respective functions. The test results indicate that the component integration performed smoothly, where the ESP8266 microcontroller was able to process time data, control servo motor movement, display information on the LCD, and receive as well as execute commands directly from the application. Therefore, this device can serve as an efficient solution to support themodernization of poultry farming through IoT-based technology